AB0188 Atherosclerosis and Cardiovascular Disease in Systemic Lupus Erythematosus. Effects of Statins Treatment. (10th June 2014) - Barbarroja, N.; Ruiz-Limon, P.; Perez-Sanchez, C.; Aguirre, M.A.; Khamastha, M.A.; Rodriguez-Ariza, A.; Gonzalez-Reyes, J.A.; Kraiwesh, H.; Villalba-Montoro, J.M.; Collantes-Estevez, E.; Cuadrado, M.J.; Lopez-Pedrera, C.
Abstract : Background: Statins may have beneficial vascular effects in systemic lupus erythematosus (SLE) beyond their cholesterol-lowering action, although involved mechanisms remain incompletely understood Objectives: To investigate the potential mechanisms participating in the efficacy of fluvastatin in preventing atherothrombosis in SLE Methods: Eighty five SLE patients and 62 healthy donors were included in the study. Selected SLE patients (n=27) received 20 mg/day fluvastatin for one month. Blood samples were obtained before the starting and at the end of treatment. Parallel in vitro studies were conducted to evaluate the underlying mechanisms involved in the response to the fluvastatin treatment Results: Increased prothrombotic and inflammatory parameters were found in SLE patients. Gene expression analysis showed that monocytes from SLE patients were major players in the altered proinflammatory parameters. Moreover, SLE monocytes displayed altered mitochondrial membrane potential and increased oxidative stress. Correlation and association analyses demonstrated a complex interplay among autoimmunity, oxidative stress, inflammation, and increased risk of atherothrombosis in SLE. Treatment of normal monocytes with SLE serum or exogenous IFNα altered inflammatory and oxidative stress markers as well as mitochondrial membrane potential and biogenesis. Effects were stronger in SLE serum treated monocytes, particularly on thrombotic and inflammatory parameters. One-month fluvastatin treatment of SLE patients reduced SLEDAI and lipid levels, oxidative status, and vascular inflammation. Array studies on monocytes demonstrated differential expression in 799 genes after fluvastatin treatment. Novel target genes and pathways modulated by fluvastatin were uncovered, including gene networks involved in cholesterol and lipid metabolism, inflammation, oxidative stress and mitochondrial activity. Electron microscopy analyses showed increased density volume of mitochondria in monocytes from fluvastatin-treated SLE patients, which also displayed higher expression of genes involved in mitochondrial biogenesis. The in vitro treatment of monocytes purified from SLE patients with fluvastatin showed similar results to in vivo studies, including reduced inflammatory and oxidative stress parameters and induced gene changes similar to those observed in the microarray analysis. Furthermore, mitochondrial biogenesis was also increased, as indicated by EM analysis and the increased expression of specific genes Conclusions: Our overall data suggest that fluvastatin improves the impairment of a redox-sensitive pathway participating in processes that collectively orchestrate the pathophysiology of atherothrombosis in SLE Acknowledgements: Supported by: P08-CVI-04234, CTS-7940, PI12/01511 and the Spanish Rheumatology Society Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4340